Why E-Wom and product quality leverage purchase intention of beauty market? Evidence brand image as a mediator through E-Commerce in Indonesia - Mangruwa, Rajiv Dharma; A Mansor, Nur Naha; Husin, Noor Hassanah; Yasmin, Savira (International Journal of Accounting, Finance and Business, 2025)
The consumer purchasing power has shifted, leading to an increase in online purchasing intentions compared to the COVID-19 period. The cosmetics industry in Indonesia has seen notable effects on consumer purchase intention, with Brand X emerging as a prominent player. Surprisingly, although the product is considered new in the market, the Brand X achieved the highest sales in the facial moisturizer category on e-commerce platforms in Indonesia. This study examines the influence of electronic word-of-mouth (eWOM) and product quality on the purchase intentions for Brand X’s moisturizer among e-commerce users in Bandung. The research sampled 200 respondents who use and purchase Brand X moisturizers online, specifically targeting individuals residing in Bandung. Data were processed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 4.0 software. Findings indicate that eWOM and product quality both significantly impact purchase intention, with brand image also playing a critical role. The study aims to offer insights for Brand X to enhance its e-commerce marketing strategies by leveraging these factors. Future research is encouraged to consider Brand X in more detailed case studies how consumer preferences and behaviors influence the cosmetic industry.